2021
DOI: 10.3390/ijms221810106
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Neutrophil Activation Requires Two Simultaneous Activating Stimuli

Abstract: Neutrophils are abundantly present in the synovium and synovial fluid of patients suffering from arthritis. Neutrophils can be activated by a multitude of stimuli and the current dogma states that this is a two-step process, consisting of a priming step followed by an activation step. Considering that neutrophil activation occurs in an inflammatory environment, where multiple stimuli are present, we argue that a two-step process is highly unlikely. Here, we indeed demonstrate that neutrophils require simultane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 60 publications
(70 reference statements)
2
38
0
Order By: Relevance
“…Thus, to increase the significance of our findings we examined whether engagement of CRIg promoted the release of NETs. In these studies, we used GM-CSF as a priming agent since this has been shown to increase the expression of CRIg ( Figure 3 ), but not the release of NETs ( 18 ). To view the release of NETs, the DNA dye PI and granule constituent, MPO, were measured in treated cells, both microscopically and by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, to increase the significance of our findings we examined whether engagement of CRIg promoted the release of NETs. In these studies, we used GM-CSF as a priming agent since this has been shown to increase the expression of CRIg ( Figure 3 ), but not the release of NETs ( 18 ). To view the release of NETs, the DNA dye PI and granule constituent, MPO, were measured in treated cells, both microscopically and by flow cytometry.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in our previous study, donor-to-donor variation exists in Th17 cell induction by neutrophils ( 9 ). This could depend on the ability of neutrophils to become activated in co-culture to secrete neutrophil elastase ( 9 ), among others, given that neutrophil activation in response to diverse stimuli varies between healthy donors as well ( 43 ). Our observations are in line with two studies demonstrating reduced Th17 cell development by VD3-treated DCs.…”
Section: Discussionmentioning
confidence: 99%
“…ROS is an important regulator of NET formation [70]; however, E. faecalis -induced ROS does not lead to NETosis. This is not unprecedented, given that neutrophils stimulated with GM-CSF and LPS also produce intracellular ROS that does not coincide with NET formation [71]. One potential explanation is that E. faecalis -induced ROS accumulates within phagosome which, together with fusion of primary granules to the phagosome [72, 73], could result in sequestration of NETosis activators such as neutrophil elastase (NE) and myeloperoxidase (MPO) [74], eventually leading to the inhibition of S. aureus -induced NETosis in mixed-infection.…”
Section: Discussionmentioning
confidence: 99%